Bis{benzyl 3-[(1H-indol-3-yl)methyl-idene]dithio-carbazato-κN,S}palladium(II) N,N-dimethyl-formamide disolvate. - Khaledi, H.; Mohd A, H. (International Union of Crystallography, 2010)
In the title compound, [Pd(C(17)H(14)N(3)S(2))(2)]·2C(3)H(7)NO, the deprotonated Schiff base ligand acts as an N,S-bidentate chelate, forming a five-membered ring with the metal atom. The Pd(II) ion, located on an inversion center, is four-coordinated by two of the Schiff base ligands in a square-planar geometry. In the crystal, the indolic NH groups are bonded to the dimethyl-formamide (DMF) solvent mol-ecules via an N-H⋯O inter-action. In addition, C-H⋯S inter-actions are observed.